Motif Hijrah Generasi Z: Studi Kasus Followers Tiktok @Hanan_Attaki_ - Kusumawati, Reni; Suseno, Ari; Riza Gusti Rahayu (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to explore the migration motives that underlie generation Z in following Ustadz Hanan Attaki's TikTok account. Alfred Schutz's phenomenological study was used as a theoretical framework to understand the motives and subjective experiences of the informants. The research method used was a qualitative approach by conducting in-depth interviews with 9 informants who were active viewers and followed Ustadz Hanan Attaki's TikTok account from generation Z. The data collected was then analyzed based on the concept of